Effect of plasma dissociation on fluorocarbon layers formed under C4F8/Ar pulsed plasma for SiO2 etching. (11th May 2017) - Matsui, Miyako; Usui, Tatehito; Ono, Tetsuo
Abstract: We investigated the effects of gas pressure on the dissociation of C4 F8 /Ar plasma and the formations of fluorocarbon layers on etched materials by SiO2 etching using pulsed-microwave electron-cyclotron-resonance plasma. Dissociated radicals and molecules of C x F y and CF x species generated from C4 F8 /Ar plasma were measured by ion attachment mass spectrometry, which is a fragment-free method. The thickness and chemical state of the fluorocarbon layers formed on the etched materials were analyzed by X-ray photoelectron spectroscopy. Higher selective etching of SiO2 relative to Si3 N4 was possible at 2.0 Pa but not at 0.5 Pa. Thick fluorocarbon layers, which protect etched materials from ion bombardment, formed on both SiO2 and Si3 N4 surfaces; thus, both the SiO2 and Si3 N4 etching rates were reduced at a high pressure. However, the CF2 flux ratio increased while the flux ratio of C2 F2 decreased as the pressure increased. The increased flux of CF2 enhanced SiO2 etching because CF2 is the main etchant of SiO2 . This CF2 -rich plasma formed CF2 -rich fluorocarbon layers, enhancing the SiO2 etching reaction.